2020
DOI: 10.1371/journal.pone.0237177
|View full text |Cite
|
Sign up to set email alerts
|

Conserved sequence motifs in the abiotic stress response protein late embryogenesis abundant 3

Abstract: LEA3 proteins, a family of abiotic stress proteins, are defined by the presence of a tryptophan-containing motif, which we name the W-motif. We use Pfam LEA3 sequences to search the Phytozome database to create a W-motif definition and a LEA3 sequence dataset. A comprehensive analysis of these sequences revealed four N-terminal motifs, as well as two previously undiscovered C-terminal motifs that contain conserved acidic and hydrophobic residues. The general architecture of the LEA3 sequences consisted of an N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 63 publications
(96 reference statements)
1
14
0
3
Order By: Relevance
“…The protein sequences of the four AtLEA3 proteins are shown in Figure 1(a). We have highlighted the conserved motifs we had identified in a previous bioinformatics study of this protein family, and found that this family is distributed throughout the plant kingdom, including non‐vascular plants 41 . The motif shown in red is a common feature of all LEA3 proteins and is denoted the W‐motif because of a completely conserved tryptophan residue at the N‐terminus.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The protein sequences of the four AtLEA3 proteins are shown in Figure 1(a). We have highlighted the conserved motifs we had identified in a previous bioinformatics study of this protein family, and found that this family is distributed throughout the plant kingdom, including non‐vascular plants 41 . The motif shown in red is a common feature of all LEA3 proteins and is denoted the W‐motif because of a completely conserved tryptophan residue at the N‐terminus.…”
Section: Resultsmentioning
confidence: 94%
“…The magenta shows a C-terminal motif termed the DAELR motif, which was also identified in our previous study. 41 AtLEA3-1, 3-2, and 3-3 proteins possess one copy of each motif, while AtLEA3-4 appears to lack the twin-Arg motif, the motif sometimes found after the N-terminus, and has an extra copy of the W-motif. We used several disorder servers to predict disorder propensity of the AtLEA3 proteins on a per residue basis.…”
Section: Atlea3 Proteins Are Disorderedmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous results suggest that the N-terminal domain of group 1 LEA proteins may be important for proper folding during dehydration [ 38 ]. Karamjeet et al predicted the conserved domains of plant G3LEA proteins and found that there are four N-terminal conserved motifs (called MAaRS, MARS, MGRX, and M [AS] [RK], respectively), which may be the signal for group 3 protein to locate mitochondria [ 39 ]. At LEA4-5, a member of group 4 of LEAs in Arabidopsis , it has been found that their N-terminal region can undergo a transition to a partially folded state and prevent enzyme inactivation, and, interestingly, the ability to gain structure under water limiting conditions is limited to the conserved region at the N-terminal, indicating the N-terminal could function as a chaperone [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…La proteína LjIDP1 de Lotus japonicus es intrínsecamente desordenada en solución, pero cambia en condiciones de deshidratación o desnaturalizantes, adoptando una estructura de α-hélice y previniendo la inactivación de enzimas al evitar que formen agregados o pierdan su conformación (Haaning et al 2008). Recientemente se ha identificado que este grupo, además de contener el dominio Pfam PF03242, se definen por la presencia de un motivo W (Trp) (Singh & Graether 2020) y otros ubicados en las regiones N-y C-terminal.…”
unclassified